Can using a servant-leadership model of supervision mitigate against burnout and secondary trauma in the health and social care sector?. Issue 2 (18th June 2021) - Mahon, Daryl
Abstract : Purpose: This paper aims to set out a model of servant leadership that can be infused within a supervisory setting to mitigate employee burnout and negative stressful experiences in the health and social care sector. Design/methodology/approach: A brief targeted review of the literature was undertaken to assess the prevalence of burnout in the health and social care sectors. The supervision literature was also explored. The outcomes associated with servant leadership were also distilled, focusing on employee well-being. Findings: Research suggests that burnout and related concepts such as secondary trauma and compassion fatigue impact these professions disproportionately. At the same time, servant leadership is suggested to mitigate some of these factors. The author presents a conceptual model of servant leadership supervision consisting of an ideographic model of servant leadership, Servant Leadership Scale-28 (SLS-28), using the most recent meta-analysis defining this construct, and previously validated measures in the extant literature to inform its design. A Servant Leadership Supervision Scale (SLSS) is also presented aligning its use to several of the core characteristics of servant leadership practice. Research limitations/implications: In doing so, the author proposes that this approach will help reduce burnout of health and social care sector employees. Limitations are considered in light of the conceptual paper and no primary data. Practical implications: A model of servant leadership supervision that can be infused into health and social care supervision. Originality/value: This is the first model of servant leadership supervision articulated for the health and social care sector.